Implications of Daily Market Statistics on Daily Stock Market Index: Empirical Evidence from Colombo Stock Exchange - Larojan, C.; Thayaparan, A. (Asian Institute of Research, 2019)
This study examined the implications of stock market statistics on share price index, using daily data for the period from 1/03/1994 to 9/28/2018 (5932 Observations) on the Colombo Stock Exchange (CSE). The main objectives of the study were to assess the significant relationship between stock market statistics and share price index and to investigate the co-integration between the variables. The study adopted the ex-post facto research design. Daily market capitalization, daily share traded, and daily turnover equity was used as the proxies for the stock market statistics. Daily All Share Price Index (ASPI) was used as the proxy for the stock price index. Augmented Dickey Fuller test was used to find out the stationery of the data series, and the results of the test showed that ASPI data and stock market statistics were stationary. The Granger Causality test was used to check any causal relationship between variables revealed that, there is a one-way causal relationship between variables. The result of the regression shown that daily market capitalization was found to be a significant positive relationship with ASPI, daily share traded equity was found to be an insignificant relationship with ASPI and daily turnover equity was found to be an insignificant relationship with ASPI. In line with the findings of this study, it recommends that the CSE should build policies and potential investors should make the strategies in terms of share trading volume to enhance the stock market liquidity.
Keywords: Colombo Stock Exchange (CSE); Daily All Share Price Index (ASPI); Daily market capitalization; Daily share traded equity; Daily turnover equity.